Improving Understanding of Intellectual Property Commercialization to High School and Vocational School Teachers and Students - Irawaty Irawaty; Wara Dyah Pita Rengga; Dani Muhtada; Duhita Driyah Suprapti; Yoris Adi Maretta (Universitas Negeri Semarang, 2025)
Understanding how to leverage intellectual property for economic gain has become increasingly urgent, as the 21st century, a digital technology era, has made creativity and innovation a highly potential source of capital. Based on the issues outlined above, it is crucial to implement activities to enhance understanding of intellectual property and its use to generate income for the community. This community service activity will target high school and vocational school students and teachers in Semarang City. The current curriculum accommodates and is relevant to intellectual property. Furthermore, various scientific competitions have been held, resulting in diverse creative and innovative outcomes. These activities, designed to enhance teachers' and students' understanding of intellectual property and its commercialization, are delivered through presentations by the team and resource persons. To find out the results and potential impact of the activity, after the presentation of the material, a questions and answers session was held with questions regarding the material that had been given. The planned activity was attended by participants consisting of high school/vocational high school teachers and high school/vocational high school students in Semarang City/Regency totalling 100 people. The activity was held on 18 July 2024, on the 3rd Floor of the UNNES LPPM Building. The activity began after being opened by the Secretary of UNNES LPPM. As speakers at the activity were the Head of the Central Java Provincial Education and Culture Office, the Head of the Human Resources Division of the Central Java Provincial Education and Culture Office, the Head of the Vocational High School Section of the Central Java Region I Education Office Branch, and the Chairperson of the Center for Innovation, IP, and Commercialization. The four speakers delivered material guided by a moderator from the community service team.